Enantio- and diastereoselective catalytic alkylation reactions with aziridines. - Moss, T; Fenwick, DR; Dixon, D (2008)
The first asymmetric phase transfer catalyzed alkylation reaction of a range of carbon acids with N-sulfonyl aziridines is reported. When 10 mol % of a cinchona derived quaternary ammonium salt was employed as the catalyst under mildly basic conditions, N-o-(trifluoromethane)benzenesulfonyl aziridine was efficiently ring-opened to afford the amino ethylene products in consistently high yields and high enantioselectivities (up to 97% ee). By employing substituted aziridines in single enantiomeric form, the corresponding enantiopure alkylation products could be obtained with a range of pronucleophiles in high yields and moderate to high diastereoselectivities (up to 30:1 dr).